Incidence and Phenotype at Diagnosis of Very-early-onset Compared with Later-onset Paediatric Inflammatory Bowel Disease: A Population-based Study [1988–2011]. (7th December 2016) - Bequet, E.; Sarter, H.; Fumery, M.; Vasseur, F.; Armengol-Debeir, L.; Pariente, B.; Ley, D.; Spyckerelle, C.; Coevoet, H.; Laberenne, J. E.; Peyrin-Biroulet, L.; Savoye, G.; et al.
Abstract: Background and Aims: Very-early-onset inflammatory bowel disease [VEO-IBD] is a form of IBD that is distinct from that of children with an older onset. We compared changes over time in the incidence and phenotype at diagnosis between two groups according to age at IBD diagnosis: VEO-IBD diagnosed before the age of 6 years, and early-onset IBD [EO-IBD] diagnosed between 6 and 16 years of age. Methods: Data were obtained from a cohort enrolled in a prospective French population-based registry from 1988 to 2011. Results: Among the 1412 paediatric cases [< 17 years], 42 [3%] were VEO-IBD. In the VEO-IBD group, the incidence remained stable over the study period. In contrast, the incidence of EO-IBD increased from 4.4/10 5 in 1988–1990 to 9.5/10 5 in 2009–2011 [+116%; p < 10 –4 ]. Crohn's disease [CD] was the most common IBD, regardless of age, but ulcerative colitis [UC] and unclassified IBD were more common in VEO-IBD cases [40% vs 26%; p = 0.04]. VEO-IBD diagnosis was most often performed in hospital [69% vs 43%; p < 10 –3 ]. Rectal bleeding and mucous stools were more common in patients with VEO-IBD, whereas weight loss and abdominal pain were more frequent in those with EO-IBD. Regarding CD, isolated colonic disease was more common in the VEO-IBD group [39% vs 14%; p = 0.003]. Conclusions: In this large population-based cohort, the incidence of VEO-IBD was low and stable from 1988 to 2011, with a specific clinical presentation. These results suggest a probable genetic origin for VEO-IBD, whereas the increase in EO-IBD might be linked to environmental factors.